τ→ π π π ντ decays in the resonance effective theory - Gómez Dumm, Daniel Alberto (2004)
τ→ π π π ντ decays are analyzed within the framework of the resonance effective theory of QCD. We work out the relevant Lagrangian that describes the axial-vector current hadronization contributing to these processes, in particular the local [Formula Presented]-Goldstone interactions. The new coupling constants are constrained by imposing the asymptotic behavior of the corresponding spectral function within QCD. Hence we compare the theoretical framework with the experimental data, obtaining a good quality fit from the ALEPH spectral function and branching ratio. We also get values for the mass and on-shell width of the [Formula Presented] resonance. In this way we are able to provide the structure functions that have been measured by OPAL and CLEO-II and we find an excellent agreement.